Counselor and Drug Detox Inpatient Verbal Behaviors in a Single Session of Motivational Interviewing and Subsequent Substance Use-Related Patient Outcomes. - Berman, Anne H.; Lindqvist, Helena; Källmén, Håkan; Durbeej, Natalie; Hermansson, Ulric; Forsberg, Lars (International Journal of Mental Health & Addiction, 2019)
Effects of counselor and client verbal behaviors, in a single motivational interviewing (MI) session during inpatient detoxification, were evaluated in relation to 17 study participants' self-reported drug use 3 months later. Also, counselor-to-client transitions in the single MI session were explored for 24 participants, using the Motivational Interviewing Sequential Code for Observing Process Exchanges (MI-SCOPE) coding instrument. Surprisingly, counselor neutral/double-sided reflections predicted lower levels of drug use (r = − 0.42), higher treatment interest (r = 0.40), and self-efficacy for abstaining from drug use when experiencing positive feelings (r = 0.48) and negative feelings or craving (r = 0.40). Client change talk predicted motivation to change (r = 0.42) and perceptions of negative aspects of drug use (r = 0.44), while higher levels of client sustain talk predicted lower levels of drug use (r = − 0.45) and lower interest in treatment (r = − 0.68). The counselor-client transition analysis showed an odds ratio (OR) of 13.84 (95% CI 9.75; 19.66) for client change talk in response to counselor reflections on change talk (RCT), and an OR of 55.98 (95% CI 26.53; 118.12) for client sustain talk in response to counselor reflections on sustain talk (RST). Future research should increase sample size and extend follow-up.